2019
DOI: 10.2196/12070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personal Health Records and Wearables on Health Outcomes and Patient Response: Three-Arm Randomized Controlled Trial

Abstract: Background Although using the technologies for a variety of chronic health conditions such as personal health record (PHR) is reported to be acceptable and useful, there is a lack of evidence on the associations between the use of the technologies and the change of health outcome and patients’ response to a digital health app. Objective This study aimed to examine the impact of the use of PHR and wearables on health outcome improvement and sustained use of the health ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 18 publications
0
43
0
3
Order By: Relevance
“…The future treatment and diagnosis of this disease will be based on the use of Apps (Lim and Pack 2017), as shown by Kim et al (2019) We currently recommend that our patients use the App simultaneously with other daily diagnosis tools (Camacho et al 2015b) to provide objective feedback of their progress in their activity. One of the great advantages of this App is the possibility of contacting a therapist who can observe the daily evolution of the patients' exercises.…”
Section: Discussionmentioning
confidence: 99%
“…The future treatment and diagnosis of this disease will be based on the use of Apps (Lim and Pack 2017), as shown by Kim et al (2019) We currently recommend that our patients use the App simultaneously with other daily diagnosis tools (Camacho et al 2015b) to provide objective feedback of their progress in their activity. One of the great advantages of this App is the possibility of contacting a therapist who can observe the daily evolution of the patients' exercises.…”
Section: Discussionmentioning
confidence: 99%
“…All three included sleep apnea trials were randomized. Kim et al (2019) 61 was conducted in South Korea (43 patients enrolled, 4-week followup, median patient enrollment month July 2017), Mendelson et al (2014) 47was conducted in France (107 patients enrolled, 17-week followup, median patient enrollment month October 2010), and Cho et al (2018) 62was conducted in South Korea (47 patients enrolled, 4-week followup, median patient enrollment month September 2016).…”
Section: Study Designs: Sleep Apneamentioning
confidence: 99%
“…The next sections describe additional aspects of these trials, which are tabled in detail in Appendix Table C -17, C-18, and C-19. Kim et al (2019) 61 included obese/overweight adults with sleep apnea who could use a mobile app and a wearable device. Mendelson et al (2014) 47 included adults with sleep apnea and BMI <40 kg/m 2 with a high cardiovascular risk score (cardiovascular risk SCORE >5%) or history of cardiovascular disease.…”
Section: Study Designs: Sleep Apneamentioning
confidence: 99%
“…Existing empirical studies of wearables in health care demonstrate the feasibility of creating technologies [ 14 ] and running data analytics [ 15 , 16 ]; small pilot studies have demonstrated the use of wearables in managing specific chronic conditions, including diabetes and high blood pressure, as well as contributing to data analytics [ 17 - 20 ]. There is also some evidence from trials that wearables can promote healthy behavior [ 21 - 23 ]. However, because these technologies have transformative potential, and there is limited adoption experience, their ultimate outcomes and significance cannot reliably be assessed at this moment.…”
Section: Introductionmentioning
confidence: 99%